2006
DOI: 10.1007/s00213-006-0322-6
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxymethamphetamine (MDMA) neurotoxicity in rats: a reappraisal of past and present findings

Abstract: Rationale3,4-Methylenedioxymethamphetamine (MDMA) is a widely abused illicit drug. In animals, high-dose administration of MDMA produces deficits in serotonin (5-HT) neurons (e.g., depletion of forebrain 5-HT) that have been interpreted as neurotoxicity. Whether such 5-HT deficits reflect neuronal damage is a matter of ongoing debate.ObjectiveThe present paper reviews four specific issues related to the hypothesis of MDMA neurotoxicity in rats: (1) the effects of MDMA on monoamine neurons, (2) the use of “inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
261
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(283 citation statements)
references
References 132 publications
(202 reference statements)
18
261
0
4
Order By: Relevance
“…Administration of MDC increased dopamine and 5-HT as well, but weakly compared with methylone. The microdialysis data with MDC are generally consistent with its lower potency at DAT and SERT but differ from results obtained with MDA (Baumann et al, 2007;Kankaanpaa et al, 1998;Nash and Nichols, 1991). For example, Kankaanpaa et al (1998) showed that MDA administration to rats induced elevations in extracellular dopamine and 5-HT in the nucleus accumbens that were greater than those produced by MDMA.…”
Section: Discussionmentioning
confidence: 61%
“…Administration of MDC increased dopamine and 5-HT as well, but weakly compared with methylone. The microdialysis data with MDC are generally consistent with its lower potency at DAT and SERT but differ from results obtained with MDA (Baumann et al, 2007;Kankaanpaa et al, 1998;Nash and Nichols, 1991). For example, Kankaanpaa et al (1998) showed that MDA administration to rats induced elevations in extracellular dopamine and 5-HT in the nucleus accumbens that were greater than those produced by MDMA.…”
Section: Discussionmentioning
confidence: 61%
“…By contrast, MDPV is a catecholamine-selective uptake blocker. The presence of a 3,4-methylenedioxy ring-substitution in MDPV does not confer serotonergic activity as observed with MDMA and methylone (Baumann et al, 2012;Baumann et al, 2007). Indeed, MDPV displays more than 100-fold greater potency at DAT and NET when compared with SERT.…”
Section: Discussionmentioning
confidence: 88%
“…This distinction in molecular mechanism is essential to determine for at least three reasons: (1) transporter substrates, but not blockers, are translocated into cells and evoke non-exocytotic release of transmitters via reverse transport (Rothman and Baumann, 2003a;Sitte, Freissmuth, 2010); (2) transporter substrates, but not blockers, are known to produce long-term deficits in monoamine neurons that are often viewed as neurotoxicity (Baumann et al, 2007;Fleckenstein et al, 2007); and (3) Figure 4 Effects of MDPV and cocaine on extracellular dopamine in nucleus accumbens, locomotor activity and cardiovascular parameters in conscious rats. For microdialysis studies (a, b), rats received i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamine is a substrate for MAT and can more potently affect DAT than SERT (Rothman et al, 2001;Baumann et al, 2007). Co-administration of methamphetamine with MDMA caused additive dopamine release at the striatum in rats, indicating that each drug might independently diffuse into the brain and affect dopamine levels in neurons.…”
Section: Pharmacodynamic Effects Of Mdma On Dopamine and 5-ht Levels mentioning
confidence: 99%